Penyelesaian Perkara Tapal Batas Desa (Studi Kasus Putusan Nomor: 12/G/2011/Ptun.Dps.) - I Gede Kresna Udayana; I Gusti Bagus Suryawan; I Wayan Arthanaya (Jurnal Analogi Hukum, 2019)
The problem of village boundaries is indeed often a debate in several areas in Bali, especially those that occur in Tabanan Regency. In Tabanan, boundary problems occur between Bealalang Village, Kediri District, Tabanan Regency and Pangkung Tibah Village, Kediri District, Tabanan Regency. The chaos of the boundary between Belalang and Pangkung Tibah villages began to erupt in 2009. The conflict began with a claim of 18 hectares of land in subak Belong in the Pangkungtibah area. Claims from the locusts are based on ancestral inheritance. This action had ended in the fencing of disputed land. the formulation of the problem in this study is as follows: How to Resolve State Administrative Disputes Through the efforts of State Administrative Courts on Settlement of Village Boundary Cases (Case Study of Decision Number: 12 / G / 2011 / PTUN.Dps.) and How the Judges consider decisions in the Case of a Suit Against the Settlement of a Village Boundary Case (Case Study of Decision Number: 12 / G / 2011 / PTUN.Dps.). The type of research used is the type of normative legal research. The results of the study in this discussion are as follows: State Administration Dispute Resolution Through the efforts of State Administrative Courts to Settle Village Boundary Cases (Case Study of Decision Number: 12 / G / 2011 / PTUN.Dps.) Has not fulfilled legal certainty and a sense of justice, this can be seen from the refusal by the Supreme Court. Consideration of the Judge in making a decision in the Case of the Claim Against the Settlement of the Village Boundary Case (Case Study of Decision Number 12 / G / 2011 / PTUN.Dps.) located in the Belong area, there is a lake pond located in the belong area and the existence of customary land rights in belonged land. Facts in terms of security, security and order in the belonged area. Administrative facts: the existence of land administration, namely land acquisition by investors.